(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2024)
Within the bosom of the humanities philosophy reposes and, as an academic field, it is ever so often criticized for its aloofness. In a recent book, Roudometof and Dessi (2022, 9-10) politely quip that philosophy’s engagement with the “glocal” has been “resilient,” transacted mostly “without encroaching on other fields.” Philosophy’s ostensible remoteness stems in part from its institutional affiliation with, cultivation and deployment of often forbiddingly technical tools of logical analysis. Although the academic field comprises a manifold of specialities, with resentment often arising against prohibitively technical branches, I narrow my focus to an understanding of “philosophy” as an activity engrossed in logical analysis, and I will plead as defence of this avowed postulation that by so doing, operationally as it were, I can argue that philosophy can make critical and salutary contributions to the burgeoning field of glocalization studies, which is so ably canvassed in the book edited by Roudometof and Dessi. Notwithstanding the promissory note offered above, and since my definition of philosophy may seem unduly restrictive, it is incumbent on me to disambiguate across related notions and to make an initial case as to both the plausibility and arguable pay-offs from taking philosophy in the way I just adumbrated. This is a substantive issue as it relates to a case I will be making as to what philosophy may have to offer to the study of glocalization.